The Effectiveness of Eclectic Approach in Teaching English Pronouns in Elementary Schools in Benghazi (Journal of Humanitarian and Applied Sciences, 2020)
The present study was mainly concerned with a vital area of grammar, which is teaching English pronouns effectively by testing different teaching methods and techniques. A number of studies in the literature showed different results regarding the effectiveness of some teaching methods and techniques in teaching English grammar. This study is a contribution to these studies where it tested some teaching methods in order to figure out which one assists elementary students improving their learning of English pronouns. These methods are Eclectic Teaching and Deductive Teaching. The population of this study consisted of twenty elementary students from Vision Training Center in Benghazi. The samples were divided into two groups (control group and experimental group). There were ten students in each group. The data was obtained by using the statistical program SPSS. Before conducting the treatment, a pretest was distributed among the participants. The posttest was used immediately after the treatment. The analysis of the collected data revealed that the students in the experimental group obtained higher scores in the posttest and were better than the students in the control group in terms of both grammar and speaking.
Keywords: eclectic approach; direct method; structural-situational; approach; deductive teaching